2013
DOI: 10.1188/13.cjon.19-20
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Care: A Home Hospice Benefit

Abstract: Hospice professionals are aware of the difficult transition that occurs when patients and their loved ones arrive at the end stages of metastatic cancer and desire to reach the end of life in their home. However, the actual practice of caring for someone who is dying at home requires specific skills and support from those trained in end-of-life care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
1
3
0
Order By: Relevance
“…Nevertheless, it is clinically relevant that patients who presented preoperative anxiety, probably conditioned by the diagnosis, displayed even higher anxiety levels at seven days postoperative, with a reduction in self-care activities; at 14 days postoperative, on the other hand, anxiety levels had dropped and self-care activities had increased. This seems to be in accordance with authors 10 - 11 who indicate that anxiety decreased in surgical patients with head and neck cancer at a specific point in time (fifth day postoperative). The increase in personal care, then, precedes the drop in anxiety levels.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Nevertheless, it is clinically relevant that patients who presented preoperative anxiety, probably conditioned by the diagnosis, displayed even higher anxiety levels at seven days postoperative, with a reduction in self-care activities; at 14 days postoperative, on the other hand, anxiety levels had dropped and self-care activities had increased. This seems to be in accordance with authors 10 - 11 who indicate that anxiety decreased in surgical patients with head and neck cancer at a specific point in time (fifth day postoperative). The increase in personal care, then, precedes the drop in anxiety levels.…”
Section: Discussionsupporting
confidence: 93%
“…Another aspect that stands out in total laryngectomy patients is that specific care is required, deriving from the surgery, which the patient needs to learn with a view to daily self-care. Laryngectomized patients experience different modifications, causing self-care needs and a self-care deficit, which should be solved or compensated to prevent complications, live with their disease and develop appropriately, incorporating self-care into their daily life as a fundamental tool to contribute to the maintenance of their health and improvement of their quality of life 10 - 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Our study was not designed to identify barriers to CHC use; however, previous research has suggested that maintaining qualified nursing staff for CHC services is challenging. 23 Nursing staff providing CHC services are responsible for medication adjustments and symptom management in times of patient deterioration or crisis, 24 and are required to work a minimum of eight hours. CHC services cannot be provided by contract nurses and at least half of the hours per shift must be staffed by a registered nurse, licensed practical nurse, or licensed vocational nurse, 4 which may be difficult for some hospices to ensure and sustain.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested that palliative care provision may improve the chances of people to receive care in the final days outside hospital or at home and to die there [8] [10] [11] [12] [13]. Cancer patients are more likely to receive hospice and palliative care compared to other dying patients, both in hospital settings and at home, and their chances of achieving a chosen home death are better [14] [15] [16] [17]. Also, hospice and palliative care use were associated with home death for cancer patients in European countries [1] [11].…”
Section: Introductionmentioning
confidence: 99%